Processing of DNA Double-Strand Breaks by the MRX Complex in a Chromatin Context - Casari, Erika; Rinaldi, Carlo; Marsella, Antonio; Gnugnoli, Marco; Colombo, Chiara Vittoria; Bonetti, Diego; Longhese, Maria Pia (Frontiers in Molecular Biosciences, 2019)
DNA double-strand breaks (DSBs) are highly cytotoxic lesions that must be repaired to ensure genomic stability and avoid cell death. The cellular response to DSBs is initiated by the evolutionarily conserved Mre11-Rad50-Xrs2/NBS1 (MRX/MRN) complex that has structural and catalytic functions. Furthermore, it is responsible for DSB signalling through the activation of the checkpoint kinase Tel1/ATM. Here, we review functions and regulation of the MRX/MRN complex in DSB processing in a chromatin context, as well as its interplay with Tel1/ATM.